2012
DOI: 10.1590/s1806-66902012000300001
|View full text |Cite
|
Sign up to set email alerts
|

Colonização micorrízica e nodulação radicular em mudas de sabiá (Mimosa caesalpiniaefolia Benth.) sob diferentes níveis de salinidade

Abstract: ), com 3 repetições. Os resultados obtidos indicam que: a salinidade reduziu a colonização micorrízica e a nodulação radicular das mudas de sabiá; a intensificação das condições de estresse salino aumentaram a dependência micorrízica das mudas de sabiá; a colonização das mudas de sabiá com os FMAs proporcionou aumentos na matéria seca dos nódulos radiculares da ordem de 1900%; as micorrizas arbusculares reduziram o pH após o cultivo do solo; e a adição de vermicomposto não promoveu efeito sobre a colonização m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
4
0
4
Order By: Relevance
“…This result confirms those obtained by Tavares et al (2012) and Li Fan et al (2011) when studying mycorrhizal colonisation under different levels of salinity in plants of the sabiá and strawberry respectively. Lúcio et al (2013) also saw a reduction in AMC in melon plants at levels of salinity higher than 1.63 dS m -1 .…”
Section: Resultssupporting
confidence: 90%
“…This result confirms those obtained by Tavares et al (2012) and Li Fan et al (2011) when studying mycorrhizal colonisation under different levels of salinity in plants of the sabiá and strawberry respectively. Lúcio et al (2013) also saw a reduction in AMC in melon plants at levels of salinity higher than 1.63 dS m -1 .…”
Section: Resultssupporting
confidence: 90%
“…Os resultados mostraram um pico de colonização no tratamento com CEa 1,36 dS m -1 com tendência de redução a partir deste valor (Figura 2b). Estudo desenvolvido com mudas de sabiá demonstrou que a colonização micorrízica com Glomus clarum, Gomus intraradices e Glomus AZ112 apresentou comportamento quadrático, alcançando o máximo em 1,71 dS m -1 , e a partir desse ponto ocorreu decréscimo na colonozação com o aumento dos níveis de salinidade (TAVARES et al, 2012 …”
Section: Figura 1 Matéria Seca Das Folhas (Msf) (A) Dos Caules + Peunclassified
“…Further, a study by E Mello, Silva and Saggin-Júnior (2012) emphasizes that depending on the microorganism-plant interaction, the formation of nodules of nitrogen-fixing bacteria in the gliricidia can be stimulated by the presence of an arbuscular mycorrhizal fungi (AMF). Lastly, Tavares et al (2012) observed that with a mycorrhizal colonization in Mimosa caesalpinaefolia Benth, there was an increase in the dry matter mass of the root nodules of the nitrogen-fixing bacteria by 1900%.…”
Section: Introductionmentioning
confidence: 97%